2015
DOI: 10.7314/apjcp.2014.15.23.10513
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNAs are Differentially Expressed in Hepatocellular Carcinoma Cell Lines with Differing Metastatic Potential

Abstract: (Talmadge and Fidler, 2010). A salient feature of metastasis is the ability of cancer cells to colonize specific organ sites (Hanahan and Weinberg, 2011). For instance, HCC cells metastasize to the lung more frequently than the lymph nodes. It is well recognized that the probability of metastatic seeding and growth is determined by both intrinsic genetic properties of the cancer cells involved and characteristics of the stromal microenvironment that surrounds them (Lu and Kang, 2007;Nguyen et al., 2009). Funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 77 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…Human ovarian cancer-specific transcript 2 (HOST2) is a member of LncRNAs, 2.9 kb in length, without a significant open reading frame (ORF), and it was reported to be highly expressed in human ovarian cancer [1315]. Transcriptomics analysis showed that LncRNA level in HCC tissues also showed abnormal expression patterns, samples including highly up-regulated in liver cancer (HULC) gene highly up-regulated in HCC tissues and LncRNA HEIH promotes tumour progression in HBV-related HCC and its expression level is associated with recurrence and survival of patients [16], suggesting that different LncRNA expression might be related with HCC [17,18]. However, there has been no relevant report on LncRNA-HOST2 expression in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Human ovarian cancer-specific transcript 2 (HOST2) is a member of LncRNAs, 2.9 kb in length, without a significant open reading frame (ORF), and it was reported to be highly expressed in human ovarian cancer [1315]. Transcriptomics analysis showed that LncRNA level in HCC tissues also showed abnormal expression patterns, samples including highly up-regulated in liver cancer (HULC) gene highly up-regulated in HCC tissues and LncRNA HEIH promotes tumour progression in HBV-related HCC and its expression level is associated with recurrence and survival of patients [16], suggesting that different LncRNA expression might be related with HCC [17,18]. However, there has been no relevant report on LncRNA-HOST2 expression in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…A transcriptomics analysis demonstrated that an abnormal expression of LncRNAs, such as LncRNA HEIH, in HCC tissues may promote tumor progression in patients with HBVrelated HCC. Moreover, HEIH expression is related to the recurrence and survival of HCC patients, which indicates that the expression of different LncRNAs might be associated with HCC [16,17]. The janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3) signaling pathway plays an important role in the regulation of tumorigenesis and cell survival [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…CT83 is a tumor antigen expressed in a variety of cancer tissues and testicular germ cells . The roles of SLC22A15, an organic ion transporter, and C15orf48 remain to be examined in cancer, albeit the latter one has been found to be overexpressed in a highly metastatic HCC cell line . DNER, a transmembrane protein that carries extracellular EGF‐like repeats, was identified as a Notch ligand that mediates cell–cell interactions that can act oncogenically and anti‐oncogenically .…”
Section: Discussionmentioning
confidence: 99%